Theodor Adorno and the Freudian Revisionism - Freitas, Verlaine (Veritas (Porto Alegre), 2018)
The purpose of the text is to present an interpretation of Theodor Adorno’s critical reading of authors considered revisionists of Sigmund Freud’s psychoanalytic theory, particularly Karen Horney. We discuss critically Adorno’s favorable positioning to the Freudian conception of the individual psychic nucleus in contrast to the hasty sociologization of psychoanalysis practiced by the revisionism of Karen Horney. In the final part we try to show how the Adornian perspective ends up by making, in his own way, the same mistake of a hasty sociologization of psychoanalysis he imputed to the revisionists and advocates an theoretical emphasis on the sociological realm that seems also problematic. ***Theodor Adorno e o revisionismo freudiano*** O objetivo do texto é apresentar uma interpretação da leitura crítica de Theodor Adorno sobre autores considerados revisionistas da teoria psicanalítica de Sigmund Freud, particularmente Karen Horney. Discutimos criticamente o posicionamento favorável de Adorno à concepção freudiana do núcleo individual do psiquismo em contraste com a apressada sociologização da psicanálise praticada pelo revisionismo de Karen Horney. Ao final, porém, procuramos mostrar como a perspectiva adorniana termina por incorrer, a seu modo, no mesmo equívoco de sociologização apressada da psicanálise imputado por ele aos revisionistas, além de defender uma ênfase teórica no plano sociológico que nos parece também problemática. Palavras-chave: Theodor Adorno; Sigmund Freud; Karen Horney; Psicanálise